2020
DOI: 10.1016/j.hal.2020.101829
|View full text |Cite
|
Sign up to set email alerts
|

A review of the socioecological causes and consequences of cyanobacterial blooms in Lake Victoria

Abstract: Africa is experiencing high annual population growth in its major river basins. This growth has resulted in significant land use change and pollution pressure on the freshwater ecosystems. Among them, the Lake Victoria basin, with more than 42 million people, is a unique and vital resource that provides food and drinking water in East Africa. However, Lake Victoria (LV) experienced a progressive eutrophication and substantial changes in the fish community leading to recurrent proliferation of water hyacinth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 114 publications
1
46
0
1
Order By: Relevance
“…Lagoon Aghien covers a surface area of 19.5 km 2 with a perimeter of 40.72 km, a volume of 75 km 3 and a maximum depth of 10 m [15]. Lagoon Aghien is connected with Lagoon Potou by a 5-km-long channel.…”
Section: Study Site: Lagoon Aghienmentioning
confidence: 99%
See 1 more Smart Citation
“…Lagoon Aghien covers a surface area of 19.5 km 2 with a perimeter of 40.72 km, a volume of 75 km 3 and a maximum depth of 10 m [15]. Lagoon Aghien is connected with Lagoon Potou by a 5-km-long channel.…”
Section: Study Site: Lagoon Aghienmentioning
confidence: 99%
“…[e.g. 2 , 3 ], there are very limited data available on the water quality and ecological status of most lentic ecosystems in tropical Africa. From these data, it seems that growing eutrophication of these ecosystems [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Shallow lakes have the characteristics of low water depth with strong hydrodynamic disturbance and intense lake-land, air-water and water-sediment interactions, which makes them more vulnerable to water pollution (Hatvani et al, 2020). Such phenomenon has been found in a lot shallow lakes, such as Lake Erie (North America) (Steffen et al 2014), Lake Kasimagaura (Japan) (Xu et al 2010), Lake Victoria(African) (Olokotum et al 2020)and Lake Chaohu and Taihu (China) (Qin 2020; Zhang and Kong 2015). As shallow lakes usually have the crucial functions of drinking-water source, aquaculture and irrigation, a series of protective programs have been launched to control the decline in freshwater quality (Qin 2007;Schindler 2006).…”
Section: Introductionmentioning
confidence: 96%
“…Lake Victoria (LV), being one of the fresh water lake body in Africa, is reported to have an increase bloom forming cyanobacteria throughout the year with the ability to produce hazardous cyanotoxins [31]. Around Lake Victoria region there are undocumented claims of cyanotoxin poisoning as a result of cyanobacteria that need to be ascertained [48]. This observation is based on studies by Mchau et al [49] on Lake Victoria waters who reported that the concentration of cyanobacteria cells were beyond the (WHO) recommended limits; for instance species of Microcystis aeruginosa ranged from 90,361.63 to 3,032.031.65 cells/mL and Anabaena spp.…”
Section: Cyanobacteria Harmful Algal Bloomsmentioning
confidence: 99%
“…Therefore, their primary route of exposure to animals is via oral consumption of contaminated water, vegetables and aquatic organism such as (fish, crustaceans and mollusks) [22]. For instance, it is evident that MCs primarily accumulate in fish livers, but can also be detected in muscles and viscera [48]. According to Drobac et al [45] ,toxin accumulation in fish tissues of the commercial species Liza sp.…”
Section: Human Microcystin Exposurementioning
confidence: 99%